2017
DOI: 10.1186/s40634-017-0103-7
|View full text |Cite
|
Sign up to set email alerts
|

Is digital photography an accurate and precise method for measuring range of motion of the hip and knee?

Abstract: BackgroundAccurate measurements of knee and hip motion are required for management of musculoskeletal pathology. The purpose of this investigation was to compare three techniques for measuring motion at the hip and knee. The authors hypothesized that digital photography would be equivalent in accuracy and show higher precision compared to the other two techniques.MethodsUsing infrared motion capture analysis as the reference standard, hip flexion/abduction/internal rotation/external rotation and knee flexion/e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 31 publications
(80 reference statements)
1
11
0
Order By: Relevance
“…However, studies have evaluated the precision and reliability of a virtual physical examination and this is done by having the patient go through a series of range of motion and by assessing mobility with a virtual goniometer. [18] Dent et al studied 52 healthy control patients who underwent elbow range-of-motion measurements in person, through teleconference, and still photography. The authors reported high inter-method reliability between teleconference-based goniometry and in-person measurements.…”
Section: Advantages Of Teleorthopedicsmentioning
confidence: 99%
“…However, studies have evaluated the precision and reliability of a virtual physical examination and this is done by having the patient go through a series of range of motion and by assessing mobility with a virtual goniometer. [18] Dent et al studied 52 healthy control patients who underwent elbow range-of-motion measurements in person, through teleconference, and still photography. The authors reported high inter-method reliability between teleconference-based goniometry and in-person measurements.…”
Section: Advantages Of Teleorthopedicsmentioning
confidence: 99%
“…Digital photography followed by joint angle quantification through an image manipulation software has been shown to have equivalent accuracy and near-equivalent precision compared to visual estimation and goniometry of hip ROM. 33 …”
Section: Hipsmentioning
confidence: 99%
“…Digital photography followed by joint angle quantification through an image manipulation software has been shown to have equivalent accuracy and nearequivalent precision compared to visual estimation and goniometry of hip ROM. 33 Several smartphone applications display good-toexcellent inter-and intra-rater reliability in the majority of hip movements as well as good-to-excellent validity when compared to a universal goniometer, digital inclinometer, and motion tracking system. [34][35][36][37][38][39][40][41][42] Among the apps currently available for download are "Clinometer + Bubble Level" (Peter Breitling, Plaincode; AppStore, Google Play), "Accurate Compass" (Ngo Na, PVD Apps; AppStore, Google Play), "PT Goniometer" (Mark Busman; AppStore) as well as "Compass" (Apple; AppStore) and "Measure" (Apple; AppStore).…”
Section: Rom Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…The accuracy of telehealth tools to determine pain, swelling, range of motion, strength, balance, and gait has been found to be valid, reliable, and feasible [5,11]. Prior studies have shown there is high agreement between in-person measurements and virtual evaluation of range of motion measurements and assessment of function for the shoulder, elbow, hip, and knee [15]. Furthermore, the use of telemedicine for orthopedic evaluation has been shown to be cost-effective, particularly when considering travel time for patients [1,10].…”
Section: Sideline Evaluation Of Musculoskeletal Injurymentioning
confidence: 99%